A new dual-channel ratiometric fluorescent chemodosimeter for Cu2+ and its imaging in living cells. Issue 47 (23rd November 2016) - Fan, Zheng; Ye, Jia-Hai; Bai, Yang; Bian, Song; Wang, Xiaolong; Zhang, Wenchao; He, Weijiang
Graphical abstract: Highlights: A new ratiometric chemodosimeter 1 was developed for recognizing Cu 2+ efficiently. Chemodosimeter 1 works well within a wide range pH and physiological conditions. 1 shows high selectivity and low detection limitation (0.2 μM) in aqueous medium. 1 can be successfully utilized in fluorescent imaging in living cells for Cu 2+ detection. Abstract: A new BODIPY derivative bearing hydrazone and hydrazide moieties was developed as an efficient dual-channel ratiometric fluorescence chemodosimeter1 for Cu 2+ in neutral aqueous medium via Cu 2+ -mediated hydrolysis of CN bond in hydrazone unit. Confocal microscopy experiments have demonstrated that chemodosimeter1 could also be used in live cells for the fast detection of Cu 2+ .